Planning of Terminal Construction at the Port of Ploce - Dundović, Čedomir; Kovačić, Mirjana (Promet - Traffic&Transportation, 2007)
The paper presents a systematic and comprehensive analysisof both the technological justification for the constructionof a container/multi-purpose terminal and a dry bulk terminal,and the efficiency of loading/unloading facilities. The organisationof Croatian ports is inefficient and the technology usedin outdated. Traffic links with the mainland, the continent andthe world are unsatisfactory, with traffic infrastructure impactingadversely on operational efficiency. Analysis results of thepresent condition of port traffic and the influence of traffic onport operations and development indicate that the Port ofPlace lacks a multi-purpose terminal that would enable modemcontainer traffic. Because of the inefficient cargo-handlingprocedure and manner of storing bulk cargo in the Port ofPlace, it is necessary to plan the construction of a coal andiron ore terminal taking into account spatia technological,economic and ecological development factors. The authorsalso examine the importance of regional initiatives spurringthe development of Croatia and, in particular, the port systemas part of the EU’s Pan-European transport corridor V BranchC. Research results are presented by a traffic and technologicaldesign for a container/multi-purpose terminal and dry bulkterminal capable of providing an appropriate level of servicefor all terminal users.